Fluorescence control of chitin and chitosan fabricated via surface functionalization using direct oxidative polymerization. Issue 13 (13th February 2018) - Phung Hai, Thien An; Sugimoto, Ryuichi
Abstract : The copolymer of 3-hexylthiophene (3HT) and fluorene (F) was directly grafted onto chitin and chitosan using FeCl3 as an oxidant. Abstract : The copolymer of 3-hexylthiophene (3HT) and fluorene (F) was directly grafted onto chitin and chitosan using FeCl3 as an oxidant. The properties of the grafted chitin/chitosan were characterized by Fourier transform infrared (FT-IR) spectroscopy, UV-Vis spectroscopy, fluorescence spectroscopy, X-ray diffraction analysis, thermogravimetric analysis (TGA), transmission electron microscopy-energy dispersive X-ray spectroscopy, and quantum yield measurements. The UV-Vis absorption peaks of the chitin/chitosan grafted with 3-hexylthiophene and fluorene copolymer were increasingly blue-shifted upon increasing the fluorene content and the red-shifted emission of the grafted chitin/chitosan were controlled by varying the monomers feed of the 3HT/F units. The hypsochromic and bathochromic shifts of chitin/chitosan were ascribed to the (3HT/F) moieties grafted to their surface. The quantum yield of grafted chitin/chitosan increased upon increasing the fluorene content. The TGA and XRD analysis revealed that the thermal stability and crystallinity of chitin/chitosan decreased upon grafting the copolymer of fluorene and 3-hexylthiophene. This article represents a simple route towards the surface modification of chitin and chitosan using conducting copolymers, providing multicolor chitin and chitosan via a one-step reaction.